Severe cold-water bleaching of a deep-water reef underscores future challenges for Mesophotic Coral Ecosystems - Foreman, Alan D.; Duprey, Nicolas N.; Yuval, Matan; Dumestre, Marielle; Leichliter, Jennifer N.; Rohr, Mark C.; Dodwell, Rose C.A.; Dodwell, Guy A.S.; Clua, Eric E.G.; Treibitz, Tali; Martínez-García, Alfredo (The Science of the total environment, 2024)
Elevated sea surface temperatures are causing an increase in coral bleaching events worldwide, and represent an existential threat to coral reefs. Early studies of Mesophotic Coral Ecosystems (MCEs) highlighted their potential as thermal refuges for shallow-water coral species in the face of predicted 21st century warming. However, recent genetic evidence implies that limited ecological connectivity between shallow- and deep-water coral communities inhibits their effectiveness as refugia; instead MCEs host distinct endemic communities that are ecologically significant in and of themselves. In either scenario, understanding the response of MCEs to climate change is critical given their ecological significance and widespread global distribution. Such an understanding has so far eluded the community, however, because of the challenges associated with long-term field monitoring, the stochastic nature of climatic events that drive bleaching, and the paucity of deep-water observations. Here we document the first observed cold-water bleaching of a mesophotic coral reef at Clipperton Atoll, a remote Eastern Tropical Pacific (ETP) atoll with high coral cover and a well-developed MCE. The severe bleaching (>70 % partially or fully bleached coral cover at 32 m depth) was driven by an anomalously shallow thermocline, and highlights a significant and previously unreported challenge for MCEs. Prompted by these observations, we compiled published cold-water bleaching events for the ETP, and demonstrate that the timing of past cold-water bleaching events in the ETP coincides with decadal oscillations in mean zonal wind strength and thermocline depth. The latter observation suggests any future intensification of easterly winds in the Pacific could be a significant concern for its MCEs. Our observations, in combination with recent reports of warm-water bleaching of Red Sea and Indian Ocean MCEs, highlight that 21st century MCEs in the Eastern Pacific face a two-pronged challenge: warm-water bleaching from above, and cold-water bleaching from below. [Display omitted] •We observed a severe cold-bleaching event (CBE) of Clipperton Atoll's mesophotic coral ecosystem (MCE).•CBEs represent a significant and previously-unreported threat to MCE functionality.•Changes in zonal wind strength govern the frequency and severity of CBEs in the Eastern Tropical Pacific (ETP).•Predicted increases in the frequency and strength of La Niña events will produce CBEs that threaten ETP MCE functionality.•Shallow warm-bleaching and deep cold-bleaching events driven by ENSO will force reef habitat contraction from above and below.